2000
DOI: 10.1159/000030119
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Arginine at Codon 72 of p53 Has No Prognostic Significance in Cervical Cancer

Abstract: Mutation of p53, a tumour suppressor gene, is uncommon in cervical cancer but the detection of human papillomavirus (HPV) DNA in cervical cancer is common. The findings of increased susceptibility to degradation of p53 by E6 protein of HPV16/18 in cervical cancer with homozygous arginine at codon 72 (HA72) of p53 led to this study on whether cervical cancers with HA72 were more aggressive with the increase in the rate of loss of p53 function. In 102 cervical cancers, 76.5% were HPV16/18 positive and 30% had HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
6
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
8
6
2
Order By: Relevance
“…There are no published studies on p53 polymorphism in Portuguese population, but the frequency of homozygous arginine p53 polymorphism has been reported as higher as 50% in many Caucasian groups ( 19,20, 58,59 ) in accordance with the high frequency detected in our samples. We found that p53 polymorphism has no value in predicting progression of CIN III which is in agreement with previous studies reporting that p53 polymorphism has no prognostic significance in cervical cancer ( 60,61 ) . In the present study, the p53 polymorphism was not related to HPV type, as reported by others ( 60–62 ) .…”
Section: Discussionsupporting
confidence: 90%
“…There are no published studies on p53 polymorphism in Portuguese population, but the frequency of homozygous arginine p53 polymorphism has been reported as higher as 50% in many Caucasian groups ( 19,20, 58,59 ) in accordance with the high frequency detected in our samples. We found that p53 polymorphism has no value in predicting progression of CIN III which is in agreement with previous studies reporting that p53 polymorphism has no prognostic significance in cervical cancer ( 60,61 ) . In the present study, the p53 polymorphism was not related to HPV type, as reported by others ( 60–62 ) .…”
Section: Discussionsupporting
confidence: 90%
“…We found that p53 polymorphism has no value in predicting progression of CIN III which is in agreement with previous studies reporting that p53 polymorphism has no prognostic significance in cervical cancer (60,61) . In the present study, the p53 polymorphism was not related to HPV type, as reported by others (60)(61)(62) .…”
Section: Discussionsupporting
confidence: 92%
“…In nasopharyngeal carcinoma, the Pro/Pro genotype was reported to be associated with a poor prognosis [20]. However, some studies demonstrated a poor association of p53 codon 72 polymorphism with prognosis [13,14]. In the present study, the presence of the Pro allele was associated with localized/low-grade prostate cancer, although the sample number was small.…”
Section: Discussioncontrasting
confidence: 52%